STUDY ON TlimvVO2MAX IN U16 SOCCER PLAYERS - Honceriu Cezar; Pătrășcan Alin (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2021)
Maximal oxygen uptake (VO2max) is considered an excellent indicator of performance level in the aerobic effort; its assessment is essential to determine training intensity. Along with VO2max, the evaluation of time limit running speed time with maximal oxygen uptake (TlimvVO2max) seems essential, if we wish to individualize as accurately as possible effort planning during training. 11 male players from the U16 group of a professional soccer club, with a mean age of 15.3 (± 0.8 years old), a weight of 65 (± 6.8 kg), and a heart rate (HR) at rest of 63 (±12 b/min) underwent the VAMEVAL field test under the form of a 20-m relay race to determine the maximal aerobic speed (VAM or vVO2max).Following the results obtained, we established the individual running time limits for TlimvVO2max. The best time obtained was 275 seconds, while the lowest TlimvVO2max was 120 seconds, with an average of 182 seconds, a median value of 166, and a standard deviation of 47.2. In what concerns Fcmax, the study recorded a minimal value of 184 b/min, a maximum heart rate value of 220 b/min, with an average of 204, a median value of 201and a standard deviation of 11.4 b/min. Numerous other studies report findings that are comparable to those within our research study.